5, 2′‐dibromo‐2, 4′, 5′‐trihydroxydiphenylmethanone attenuates LPS‐induced inflammation and ROS production in EA.hy926 cells via HMBOX1 induction. Issue 1 (24th October 2018) - Yuan, Hong‐Xia; Feng, Xiu‐E; Liu, En‐Li; Ge, Rui; Zhang, Yuan‐Lin; Xiao, Bao‐Guo; Li, Qing‐Shan
Abstract: Inflammation and reactive oxygen species (ROS) are important factors in the pathogenesis of atherosclerosis (AS). 5, 2′‐dibromo‐2, 4′, 5′‐trihydroxydiphenylmethanone (TDD), possess anti‐atherogenic properties; however, its underlying mechanism of action remains unclear. Therefore, we sought to understand the therapeutic molecular mechanism of TDD in inflammatory response and oxidative stress in EA.hy926 cells. Microarray analysis revealed that the expression of homeobox containing 1 (HMBOX1) was dramatically upregulated in TDD‐treated EA.hy926 cells. According to the gene ontology (GO) analysis of microarray data, TDD significantly influenced the response to lipopolysaccharide (LPS); it suppressed the LPS‐induced adhesion of monocytes to EA.hy926 cells. Simultaneously, TDD dose‐dependently inhibited the production or expression of IL‐6, IL‐1β, MCP‐1, TNF‐α, VCAM‐1, ICAM‐1 and E‐selectin as well as ROS in LPS‐stimulated EA.hy926 cells. HMBOX1 knockdown using RNA interference attenuated the anti‐inflammatory and anti‐oxidative effects of TDD. Furthermore, TDD inhibited LPS‐induced NF‐κB and MAPK activation in EA.hy926 cells, but this effect was abolished by HMBOX1 knockdown. Overall, these results demonstrate that TDD activates HMBOX1, which is an inducible protective mechanism that inhibits LPS‐induced inflammation and ROS production in EA.hy926 cells by the subsequent inhibition of redox‐sensitive NF‐κB and MAPK activation. Our study suggested that TDD may be a potential novel agent for treating endothelial cells dysfunction in AS.